Low-input technology proves viable for limited-resource farmers in Salinas Valley - Miguel Altieri; Javier A. Trujillo; Marta A. Astier; Paul Gersper; Wilhelmus A. Bakx (California Agriculture, 1991)
Low-input farming techniques offered energy-saving, cost-effective alternatives for resource-poor farmers of Mexican origin in the Salinas Valley. Most of these farmers currently manage small acreages using intensive vegetable cropping systems and high-input technologies.